2021
DOI: 10.1021/acscatal.1c01434
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Hydroxyl-Directed Hydrogenation: Control of Diastereoselectivity through Bimetallic Surface Composition

Abstract: Directed hydrogenation, in which product selectivity is dictated by the binding of an ancillary directing group on the substrate to the catalyst, is typically catalyzed by homogeneous Rh and Ir complexes. No heterogeneous catalyst has been able to achieve equivalently high directivity due to a lack of control over substrate binding orientation at the catalyst surface. In this work, we demonstrate that Pd−Cu bimetallic nanoparticles with both Pd and Cu atoms distributed across the surface are capable of high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Such dynamic surface reconstruction has previously been observed in bimetallic materials exposed to thermal annealing. [ 21 ] This is strongly supported by 57 Fe Mössbauer spectroscopy at 80 K which revealed the presence of a new Fe‐containing phase (27%) in the material after catalysis as well as a significant decrease in the amount of Fe 5 C 2 (down to 6%) (Figure 6e).…”
Section: Resultsmentioning
confidence: 56%
“…Such dynamic surface reconstruction has previously been observed in bimetallic materials exposed to thermal annealing. [ 21 ] This is strongly supported by 57 Fe Mössbauer spectroscopy at 80 K which revealed the presence of a new Fe‐containing phase (27%) in the material after catalysis as well as a significant decrease in the amount of Fe 5 C 2 (down to 6%) (Figure 6e).…”
Section: Resultsmentioning
confidence: 56%
“…Using bimetallic alloys containing a noble metal and a first-row transition metal, we envisioned that the OH directing group would preferentially bind to the more oxophilic first-row transition metal while the noble metal would still be available to activate H 2 and bind the olefin (Figure 4a). 107 We showed that careful control over surface composition in a Pd−Cu bimetallic nanoparticle enabled high diastereoselectivity in the hydrogenation of a range of cyclic homoallylic and allylic alcohols, achieving comparable diastereoselectivities in some cases to Crabtree's catalyst, [Ir(COD)(py)(PCy 3 )]PF 6 (Figure 4b). While the conformation of the substrate still had an impact on the inherent steric preferences of the hydrogenation, we were able to elucidate a general principle for directed substrate design in heterogeneous systems.…”
Section: ■ Bimetallic Catalystsmentioning
confidence: 93%
“…Recently, our group hypothesized that bimetallic catalysts with two distinct binding sites may provide a more general solution to achieve high diastereoselectivity in the OH-directed heterogeneous hydrogenation reaction. Using bimetallic alloys containing a noble metal and a first-row transition metal, we envisioned that the OH directing group would preferentially bind to the more oxophilic first-row transition metal while the noble metal would still be available to activate H 2 and bind the olefin (Figure a) . We showed that careful control over surface composition in a Pd–Cu bimetallic nanoparticle enabled high diastereoselectivity in the hydrogenation of a range of cyclic homoallylic and allylic alcohols, achieving comparable diastereoselectivities in some cases to Crabtree’s catalyst, [Ir­(COD)­(py)­(PCy 3 )]­PF 6 (Figure b).…”
Section: Bimetallic Catalystsmentioning
confidence: 99%
“…42,43 For example, Shumski and coworkers studied hydroxyl-directed hydrogenation of terpinene-4-ol over bimetallic PdCu catalysts (Figure 7), comparing diastereoselectivity with monometallic catalysts. 39 At 99% reactant conversion, PdCu displayed a dr (P 1 /P 2 ) of 16:1, while Pd/SiO 2 displayed a dr of 1:3. While conventional steric hindrance effects control diastereoselectivity over monometallic Pd sites where alkene functional groups and H atoms adsorb, the authors proposed that the OH group in terpene-4-ol binds preferentially to oxophilic surface Cu atoms in bimetallic PdCu catalysts (Figure 7b), leading to haptophilic control of diastereoselectivity in PdCu but not in Pd-only materials.…”
Section: Formation Of New Stereocenters In Reactions Ofmentioning
confidence: 95%
“…Furthermore, reactants with OH-directing groups at the pseudoaxial position in halfchair conformations exhibited a stronger directing effect and yielded a higher dr (>12:1) compared to reactants in which the directing group prefers an equatorial conformation (dr < 8:1), due to the differences in reactant−surface binding interactions. 28,39 In a separate study, Augustine showed that the reaction environment (pH, solvent) can affect hydrogenation stereochemistry by altering adsorbate binding and the mechanism of stereochemistry-determining steps. 44,45 These reports exemplify the complex interdependence between catalyst electronic and geometric properties, chiral reactant structure, and reaction conditions that together govern the diastereoselectivity in hydrogenation reactions.…”
Section: Formation Of New Stereocenters In Reactions Ofmentioning
confidence: 99%